What a veterinary graduate should know about basic and clinical pharmacology: A Delphi study to finalize day‐1 competencies. Issue 4 (20th October 2020) - Werners, Arno; Fajt, Virginia
Abstract: The recent changes in curricula in veterinary medicine have changed the delivery and focus on veterinary pharmacology and therapeutics, resulting in a perceived lack of knowledge of pharmacology and therapeutic decision making in recent graduates. To aid veterinary pharmacologists and clinicians teaching clinical pharmacology, core competencies were drafted by a working group. Following this process, a Delphi study was performed to come to a consensus on day‐1 competencies in veterinary pharmacology and therapeutics. The described competencies could be useful to a variety of stakeholders in veterinary pharmacology, including those teaching veterinary pharmacology worldwide. Secondly, they could form the basis of vertical alignment of the subject within schools and across the world, as well as serving to frame the integration of veterinary pharmacology and therapeutics into competency‐based veterinary education.